Use of a novel sediment exposure to determine the effects of triclosan on estuarine benthic communities. (10th December 2012) - Ho, Kay T.; Chariton, Anthony A.; Portis, Lisa M.; Proestou, Dina; Cantwell, Mark G.; Baguley, Jeffrey G.; Burgess, Robert M.; Simpson, Stuart; Pelletier, Marguerite C.; Perron, Monique M.; Gunsch, Claudia K.; Bik, Holly M.; et al.
Abstract Triclosan (5‐chloro‐2‐[2, 4‐dichlorophenoxy]phenol) is a relatively new, commonly used antimicrobial compound found in many personal care products. Triclosan is toxic to marine organisms at the micrograms per liter level, can photodegrade to a dioxin, can accumulate in humans, and has been found to be stable in marine sediments for over 30 years. To determine the effects of triclosan on marine benthic communities, intact sediment cores were brought into the laboratory and held under flowing seawater conditions. A 2‐cm layer of triclosan‐spiked sediment was applied to the surface, and after a two‐week exposure the meio‐ and macrofaunal communities were assessed for differences in composition relative to nonspiked cores. A high triclosan treatment (180 mg/kg dry wt) affected both the meio‐ and the macrobenthic communities. There were no discernible differences with a low‐triclosan treatment (14 mg/kg dry wt). This exposure method is effective for testing the benthic community response to sediment contaminants, but improvements should be made with regard to the amount and method of applying the overlying sediment to prevent smothering of fragile benthic organisms. Environ. Toxicol. Chem. 2013;32:384–392. © 2012 SETAC